A risk calculator predicting recurrence in lymph node metastatic penile cancer. (7th August 2020) - Bandini, Marco; Spiess, Philippe E.; Pederzoli, Filippo; Marandino, Laura; Brouwer, Oscar R.; Albersen, Maarten; Roussel, Eduard; de Vries, Hielke M.; Chipollini, Juan; Zhu, Yao; Ye, Ding‐Wei; Ornellas, Antonio A.; et al.
Abstract : Objectives: To develop and externally validate a risk calculator for prediction of any cancer recurrence in patients with penile squamous cell carcinoma (pSCC) and inguinal lymph node metastases (ILNM), as to date no validated prognostic tool is available for patients with pSCC and ILNM. Patients and Methods: The development cohort included 234 patients from seven referral centres. The external validation cohort included 273 patients from two additional referral centres. Cox regression identified predictors of any recurrence, which were used to develop a risk calculator. The risk‐calculator grouped the development and the validation cohorts according to the individual risk of any recurrence at 24 months (24m‐R). Adjuvant treatment effects were tested on overall survival (OS) according to the derived tertiles, within the development and validation cohorts. Results: Positive surgical margins, pN3, and ILNM ratio were associated with higher recurrence rate. The 2‐year OS rates were lower for patients with high (>37%) and intermediate (19–37%) compared to low (<19%) 24m‐R risk of recurrence, for both the development (43% and 58% vs 83%, P  < 0.001) and validation cohort (44% and 50% vs 85%, P  < 0.001). Results were confirmed in the subgroup of patients who did not receive adjuvant treatment ( P  < 0.001), but not in patients who did receive adjuvant treatments in both the development and validation cohorts ( P  > 0.1). Conclusion: Adjuvant treatment planning is crucial in patients with pSCC with ILNM, where only weak evidence is available. The current tool proved to successfully stratify patients according to their individual risk, potentially allowing better tailoring of adjuvant treatments.